Implication of Oxidative Stress in Fetal Programming of Cardiovascular Disease - Rodríguez-Rodríguez, Pilar; Ramiro-Cortijo, David; Reyes-Hernández, Cynthia G.; López de Pablo, Angel L.; González, M. Carmen; Arribas, Silvia M. (Frontiers in Physiology, 2018)
Lifestyle and genetic background are well known risk factors of cardiovascular disease (CVD). A third contributor is suboptimal fetal development, due to nutrient or oxygen deprivation, placental insufficiency or exposure to toxic substances during intrauterine life. The fetus adapts to these adverse conditions to ensure survival but at the cost of low birth weight. The long-term consequence is an increased susceptibility to develop hypertension, diabetes, obesity and coronary heart disease in adult life. This process is known as fetal programming of CVD and has been widely validated through numerous epidemiological studies. Experimental animal models mimicking suboptimal intrauterine conditions have provided additional evidence of the association between low birth weight and CVD and enabled exploring the underlying mechanisms. Among them, oxidative stress has emerged as a central player, participating in the response of the feto-placental unit to stress factors and in the alterations of physiological systems of cardiovascular control, ultimately leading to disease. This review aims to cover these two aspects. Firstly, the evidence from human studies of the implication of oxidative stress in low birth weight induced by suboptimal conditions during intrauterine life, emphasizing the role of the placenta. In the second part we summarize the data obtained in experimental animals exposed to various fetal stress factors regarding the alterations in oxidative balance in the kidney, the heart and the vasculature and discuss the emerging role of the mitochondria.